El entrenamiento anaeróbico láctico y su relación con las actividades agrícolas luego de las jornadas de estudio. - Orozco Yuquilema, Angelo Fernando (2023)
The present research project had the objective of identifying the benefits of lactic anaerobic training in the development of agricultural activities after the study days, knowing that students from rural areas frequently carry out activities that require strength and energy. Methodologically, a quantitative approach was used, it was bibliographic, field and cross-sectional, the design was quasi-experimental, the student population of the Educational Unit "Dr. Manuel Rodríguez Orozco, non-probabilistic and intensional sample, the techniques were the assessment tests and the instruments were the lactate test, the 1RM Test and the IPAQ Questionnaire. Based on the application of the evaluation instruments, it was possible to know that in the Pretest 70% of the students had high lactic acid; Through the application of anaerobic exercise activities in the post test, it was possible to know that 90% of the students had a normal level of lactic acid; in the application of T-student, a bilateral significance of 0.00 was observed. Coming to the conclusion that anaerobic training has a greater relationship with agricultural activities, since performing anaerobic exercises will allow better blood circulation in the body, generating lactate within its normal levels, which allows the students have greater energy and strength to carry out agricultural activities.